Characterization of the Proprotein Convertase-Mediated Processing of Peroxidasin and Peroxidasin-like Protein - Hajnal A. Kovács; Enikő Lázár; György Várady; Gábor Sirokmány; Miklós Geiszt (MDPI AG, 2021)
Peroxidasin (PXDN) and peroxidasin-like protein (PXDNL) are members of the peroxidase-cyclooxygenase superfamily. PXDN functions in basement membrane synthesis by forming collagen IV crosslinks, while the function of PXDNL remains practically unknown. In this work, we characterized the post-translational proteolytic processing of PXDN and PXDNL. Using a novel knock-in mouse model, we demonstrate that the proteolytic cleavage of PXDN occurs in vivo. With the help of furin-specific siRNA we also demonstrate that the proprotein-convertase, furin participates in the proteolytic processing of PXDN. Furthermore, we demonstrate that only the proteolytically processed PXDN integrates into the extracellular matrix, highlighting the importance of the proteolysis step in PXDN's collagen IV-crosslinking activity. We also provide multiple lines of evidence for the importance of peroxidase activity in the proteolytic processing of PXDN. Finally, we show that PXDNL does not undergo proteolytic processing, despite containing sequence elements efficiently recognized by proprotein convertases. Collectively, our observations suggest a previously unknown protein quality control during PXDN synthesis and the importance of the peroxidase activity of PXDN in this process.